(untitled) (Fiep Bulletin - online, 2015)
The Scool Physical Education teacher’s knowledge about peculiar motor characteristics from students with Cerebral Palsy (CP) is an emerging aspect when the special education needs people’s inclusion is discussed and put in practice. This work, descriptive-diagnosis of the transverse type, aimed to evaluate the gross motor function in children with CP, aged 04 to 15 years, enrolled in public regulate teaching from Florianópolis/SC, since February to May of 2005. For the motor function evaluation GMFM-88 was used, with verification of historical in pregnancy, perinatal and neonatal period done by the completion of a Form of Antecedents. 22 children were assessed, with medium age 7,9 years old, most female (63,3%), and quadriparesia the largest percentile (36,4%). In description of antecedents, was verified prematurity (19%); very low birth weight (25%); perinatal asphyxia (42,8%); diagnosis of CP only to the 5 years old (27,3%). About gross motor function, smaller scores were obtained by the cases of Quadriplegia and Coreo-atetosis, with expected value zero in functions of Standing and Walking, Running and Jumping. Girls had Score-total in larger medium value than boys, but the difference wasn’t statistically significant. To make possible the inclusion of that population in the School Physical Education is important to know their motor potentialities, elaborating planning to involve the student and prevent the reinforcement of pathological patterns of movement, promoting the quality of life of such population.